The megachurch and the mainline : remaking religious tradition in the twenty-first century - Ellingson, Stephen, 1962- (University of Chicago Press, 2007)
Religious traditions provide the stories and rituals that define the core values of church members. Yet modern life in America can make those customs seem undesirable, even impractical. As a result, many congregations refashion church traditions so they may remain powerful and salient. How do these transformations occur? How do clergy and worshipers negotiate which aspects should be preserved or discarded?. Focusing on the innovations of several mainline Protestant churches in the San Francisco Bay Area, Stephen Ellingson?s The Megachurch and the Mainline provides new understandings of the tra.